2012
DOI: 10.1007/s00508-012-0125-1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone levels as a predictor of mortality in intensive care patients: A comparative prospective study

Abstract: Calculation of APACHE II score as well as measurement of PCT, fT3, fT4 and TSH levels may all be useful as predictors of mortality in intensive care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
3
10
0
1
Order By: Relevance
“…[23] FT3, FT4, and TSH levels were all found to be associated with higher mortality in intensive care patients. [2425] Generally speaking, measurement of BUN, albumin, lactate, and FT3 levels might be useful as a predictor of mortality in intensive care patients. Those four biomarkers are expected to be included in model in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[23] FT3, FT4, and TSH levels were all found to be associated with higher mortality in intensive care patients. [2425] Generally speaking, measurement of BUN, albumin, lactate, and FT3 levels might be useful as a predictor of mortality in intensive care patients. Those four biomarkers are expected to be included in model in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Higher Apache 2 scores and poorer prognosis are reported for patients with low serum fT3 and fT4 concentrations. [18] Moreover, exogenous T3 replacement may reduce the mortality in surgery patients with sepsis. [19] Thyroid hormone and immune functions are closely interlinked.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that mortality rate increases or shows no change as suppression of thyroid hormone levels increases in intensive care unit patients. Some researchers found mortality associated with suppressed fT 3 , while another researcher suggested that suppressed fT 4 was associated with mortality, whereas some researchers have stated that both of them are associated with mortality; furthermore, fT 3 and fT 4 were better prognostic indicators than the APACHE II Scoring System (1,(22)(23)(24)(25)(26)(27). In contrast with those, it has been proposed that thyroid hormone levels are not indicators with respect to mortality (11).…”
Section: Discussionmentioning
confidence: 99%
“…The most common endocrine change in those patients is euthyroid sick syndrome. Underlying diseases, stress, ongoing medications of the patient, and impaired nutritional status may lead to primarily low free T 3 (f T 3 ) and also suppressed free T 4 (f T 4 ) and thyroid-stimulating hormone (TSH) (1). Patients hospitalized for clinical conditions, such as sepsis, malignancy, trauma, burns, myocardial infarction, and cerebrovascular events or for prolonged hunger status more than 24-36 hours, demonstrate remarkable changes in their hypothalamic-pituitary-thyroid axis and thyroid hormone levels (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%